Prevalence of falls among older adults in the Gulf Cooperation Council countries: A systematic review and meta-analysis. (July 2019) - Alqahtani, Bader A.; Alshehri, Mohammed M.; Hoover, Jeffrey C.; Alenazi, Aqeel M.
Highlights: The prevalence of falls among among older adults living in the GCC countries was around 45%. Factors such as age, female gender, low educational level, and number of medications were associated with falls. The current study provide insight on how the topic of falls is understudied in the GCC countries. Abstract: Aim: The aim of this study was to conduct a systematic review and meta-analysis for studies that have examined the prevalence and risk factors of falls in older adults living in the Gulf Cooperation Council countries (GCC). Methods: A literature search was performed using PubMed, Web of Science, Physiotherapy Evidence Database; and SCOPUS up to October 2018 to identify studies that have examined prevalence, risk factors, or consequences of falls in older adults living in the GCC. Results: A total of 6 studies met the inclusion criteria. The pooled prevalence of falls among older adults residing in GCC countries was 46.9%. Falls among included studies were associated with older age, female gender, low educational level, and number of medications. Conclusions: The study shows a high prevalence of falls in older adults living in the GCC countries. The risk factors in the current study must be interpreted with caution, since some of the included studies did not report any risk factors. Due to the limited number of evidence evaluating risk factors and consequences of falls in the GCC countries population, a further longitudinal research is needed.